Bizantyńscy intelektualiści o wojnie i pokoju (Mikołaj Mistyk i Teodor Dafnopates) - Leszka, Mirosław J. (Vox Patrum, 2021)
The letters of Nicholas Mystikos and Theodore Daphnopates/Romanos Lekapenos to Simeon, the ruler of Bulgaria, revolve around matters of war and peace. The attitude to the war that can be found in them is, however, formulaic. The war is evil and tied to bloodshed, cruelty and plunder. In this vague overview the references to the suffering of monks and nuns play a significant role. This seems to have been brought up due to the monastic episode in the life of the Bulgarian ruler. Referencing personal sentiments of Simeon were meant to shake him up and eventually convince to settle for the peace. For Nicholas Mystikos and Theodore Daphnopates/Romanos Lekapenos peace is the greatest good and in order to preserve it many concessions can be justified. There is however a boundary that should not be crossed. For Nicholas Mystikos it is the retention of sovereignty. This view is obviously shared by Theodore Daphnopates, however, he points out that the boundary should be moved further and be concerned with the preservation of the territorial integrity of the Roman state.